IBM Power Systems Security for SAP Applications - Quintero, Dino; Altevogt, Peter (IBM Redbooks, 2020)
This IBM Redpaper highlights the RAS and security features on the hardware, hypervisor, Linux, and SAP application levels. It highlights what is transparent, what needs enablement, and also the known prerequisites for the use of these features.